Pelatihan Pembuatan Produk Berbasis Hasil Perikanan di Desa Huangobotu - Asri Silvana Naiu; Nikmawatisusanti Yusuf; Wila Rumina Nento (Universitas Negeri Gorontalo, 2022)
Huangobotu Village, Kabila Bone District, Bone Bolango Regency is a village located in the Tomini Bay area, where the majority of the people work as a fishermen. During the fishing season, the catch of fish is very large, and sometimes some types of fish are not sold while others are sold at minimum prices. Communities can take opportunities in the utilization of fishery products through the processing of fishery products, so that they can help improve the community's economy. The purpose of this service is to improve the community's economy through training in making fishery product-based products which the type of processed fishery products provided during the training in the form of fish nuggets and meatballs.